Global changes in gene expression of Barrett's esophagus compared to normal squamous esophagus and gastric cardia tissues. - Paula L Hyland (PLoS ONE, 2014)
Barrett's esophagus (BE) is a metaplastic precursor lesion of esophageal adenocarcinoma (EA), the most rapidly increasing cancer in western societies. While the prevalence of BE is increasing, the vast majority of EA occurs in patients with undiagnosed BE. Thus, we sought to identify genes that are altered in BE compared to the normal mucosa of the esophagus, and which may be potential biomarkers for the development or diagnosis of BE.We performed gene expression analysis using HG-U133A Affymetrix chips on fresh frozen tissue samples of Barrett's metaplasia and matched normal mucosa from squamous esophagus (NE) and gastric cardia (NC) in 40 BE patients.Using a cut off of 2-fold and P<1.12E-06 (0.05 with Bonferroni correction), we identified 1324 differentially-expressed genes comparing BE vs NE and 649 differentially-expressed genes comparing BE vs NC. Except for individual genes such as the SOXs and PROM1 that were dysregulated only in BE vs NE, we found a subset of genes (n = 205) whose expression was significantly altered in both BE vs NE and BE vs NC. These genes were overrepresented in different pathways, including TGF-β and Notch.Our findings provide additional data on the global transcriptome in BE tissues compared to matched NE and NC tissues which should promote further understanding of the functions and regulatory mechanisms of genes involved in BE development, as well as insight into novel genes that may be useful as potential biomarkers for the diagnosis of BE in the future.